Hepatocyte growth factor in dampening liver immune‐mediated pathology in acute viral hepatitis without compromising antiviral activity. Issue 4 (April 2014) - Aguilar‐Valenzuela, Renan; Carlsen, Eric D.; Liang, Yuejin; Soong, Lynn; Sun, Jiaren
Abstract Background and Aim Hepatocyte growth factor (HGF) is a pleiotropic cytokine related with cell proliferation and survival; however, its role in viral hepatitis is not elucidated. In this study, we studied HGF immune role in viral hepatitis. Methods Mice received hydrodynamically delivered HGF plasmid or control plasmid and then infected with adenovirus, and parameters of immune‐mediated liver damage were evaluated. We studied dendritic cell (DC) activation in the presence of HGF. T cells collected from infected mice were restimulated with virally infected DC to measure cytokine production in vitro. Results HGF ameliorated the liver inflammation during viral hepatitis as alanine transferase, intrahepatic lymphocytes, and splenocyte counts were diminished by HGF. Lower histological scores of liver pathology were observed in the HGF group. DC from the HGF group expressed reduced CD40. The hepatic expression and serum concentration of IL‐12p40 were diminished in HGF‐transfected mice. In vitro experiments with DC confirmed that HGF diminished CD40 expression and IL‐12p40 production. The expression and serum levels of IFN‐γ, IL‐6 and CXCL9 were significantly decreased in the HGF group. HGF overexpression diminished the expression and concentration of IL‐10 and TGF‐β. The frequency of PD‐1+Tim‐3+ in CD8 T cells was decreased by HGF overexpression. Moreover, T cells in the HGF group at day 14 secreted more IFN‐γ and TNF‐α than those in the control group when restimulated with virally infected DC. Conclusion HGF modulated DC activation and T cell priming, thereby limiting the immune‐mediated damage in the liver. However, viral clearance was not compromised by HGF.